1989
DOI: 10.1136/thx.44.6.461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an external resistance on maximum flow in chronic obstructive lung disease: implications for recognition of coincident upper airway obstruction.

Abstract: To determine how the presence of generalised airflow limitation due to chronic obstructive lung disease affects the recognition of simulated upper airway obstruction, a study was carried out in 12 patients (mean (SD) age 57 (7) years) with chronic obstructive lung disease (FEV, % predicted 53 (22), range 21-70) and 12 matched control subjects. Patients and control subjects performed maximal inspiratory and expiratory flow-volume curves in a variable volume plethysmograph with and without upper airway obstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It is known how dynamic lung function, as reflected by maximal flow volume loops, changes with fixed or variable narrowing of extrathoracic airways. [13][14][15][16][17] However, the effect of increased extrathoracic resistance on the indices of tidal flow/time patterns has not yet been described. In this observational study we have added a single, fixed, large resistance to the expiratory line.…”
Section: And (Ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known how dynamic lung function, as reflected by maximal flow volume loops, changes with fixed or variable narrowing of extrathoracic airways. [13][14][15][16][17] However, the effect of increased extrathoracic resistance on the indices of tidal flow/time patterns has not yet been described. In this observational study we have added a single, fixed, large resistance to the expiratory line.…”
Section: And (Ii)mentioning
confidence: 99%
“…Obstruction during expiration alone is rare but does occur in vocal cord dysfunction 12 and in pursed lip breathing. It is known how dynamic lung function, as reflected by maximal flow volume loops, changes with fixed or variable narrowing of extrathoracic airways 13–17 . However, the effect of increased extrathoracic resistance on the indices of tidal flow/time patterns has not yet been described.…”
Section: Introductionmentioning
confidence: 99%
“…Robertson et al 4 studied the effects of an external resistance on ventilatory function in normal controls and patients with COPD. They also found that PEF was the most sensitive index to the presence of an external resistance when the internal diameter of an resistor was decreased to 12 mm in the control group and 10 mm in the COPD group, with significant reductions whether expressed in absolute units or as a percentage change.…”
Section: Discussionmentioning
confidence: 99%
“…Zwi et al 6 found that the maximum voluntary ventilation fell when artificial flow restrictors were inserted into the breathing circuit, and Robertson et al 4 reported similar reductions in peak expiratory flow (PEF) and mid expiratory flow (MEF 50% ), whereas the forced expiratory volume in one second (FEV 1 ) was little affected unless the added restrictor had an orifice of less than about 8 mm.…”
mentioning
confidence: 97%